From local control to immune modulation: hypofractionated radiotherapy as a backbone for cancer immunotherapy - Zhuang, Xiaoxuan; Sun, Yao; Zhuang, Dayong (Frontiers in Oncology, 2026)
Hypofractionated radiotherapy (HFRT) is increasingly used not only for local tumour control but also for its immunomodulatory potential. By delivering higher doses per fraction over fewer sessions, HFRT improves local disease control and reshapes the tumour immune microenvironment. This review integrates preclinical, translational, and clinical evidence on the immunological effects of HFRT when combined with immune checkpoint inhibitors (ICIs) and other immune-based therapies. Available evidence indicates that HFRT induces immunogenic cell death and activates the cGAS-STING pathway, enhancing dendritic cell priming and CD8+ T-cell trafficking. These processes are most likely to translate into systemic antitumour activity when checkpoint blockade is delivered with an appropriate peri-radiotherapy window. Under these conditions, HFRT may facilitate immune conversion of selected “cold” tumours, particularly in combination with PD-1/PD-L1 blockade. Clinical outcomes remain heterogeneous across tumour types. Improved out-of-field responses and survival signals have been reported in non-small-cell lung cancer, head and neck squamous cell carcinoma, and triple-negative breast cancer, whereas tumours dominated by myeloid-driven or stromal suppression, such as pancreatic ductal adenocarcinoma, show limited benefit. From a clinical design perspective, effective HFRT-immunotherapy combinations require careful selection of fractionation, timing, and radiation geometry. Fractionation should preserve DNA sensing and dendritic-cell activation, checkpoint therapy should align with the peri-radiotherapy window, and radiation delivery should minimise immune suppression by sparing tumour-draining lymph nodes and limiting unnecessary low-dose exposure. HFRT can serve as a practical backbone for immune-based therapies when these variables are appropriately aligned.